KEMISKINAN DAN PERILAKU KEAGAMAAN DALAM MENGUNGKAP SIMBOL KEAGAMAAN PENGEMIS - Suhandi, Suhandi; Erlita, Dewi (Universitas Islam Negeri Raden Intan Lampung, 2021)
Poverty is a social problem that is always present in the midst of society, and has always been a very interesting topic for discussion and study of the development of human life from time to time. In addition to displaying impressions such as pleading facial expressions to attract the sympathy of buyers and market traders, religious symbols are often used as attributes of begging such as caps, headscarves, and prayers. This paper will discuss the factors that make beggars a livelihood, and look further at the work of begging for their religious behavior. This study uses a qualitative descriptive method, with the type of field research and a case study research design. Data collection uses three techniques, namely: observation, interviews, and documentation. Data analyisis through data reduction, data display, and conclusion drawing / verification. The results of the study indicate that someone does something caused by various factors such as physical disability, low education level, lack of skills, friends, and the assumption that begging is a lawful job. The influence of begging activities on the behavior of religious beggars such as prayer, fasting, and zakat implementation, although in the practice of begging they often use religious symbols such as hats, headscarves, reading prayers, but in their lives they do not actually carry out their behavior in accordance with the teachings of their religion, symbols The religious symbols used will display the figure of a religious beggar, which is used as a sympathy puller to get people's sympathy.